Maze Games in Improving Writing Ability in Early Children - Yuniasih Yuniasih; Aini Loita; Nuraly Masum Aprily (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
The goal of this study is to learn more about the role of maze games in boosting early childhood writing skills. This article uses a qualitative approach and the data collection technique used is observation and interviews. Based on the analysis it was found that Wijaya Kusumah Kindergarten in using maze game media can be an interesting learning alternative in improving children's writing skills, carried out with children assigned to follow a predetermined path. Teachers must be creative in making interesting and fun activities to develop children's writing skills.